Elaborating on theory with middle managers' experience implementing healthcare innovations in practice. (December 2015) - Birken, Sarah; DiMartino, Lisa; Kirk, Meredith; Lee, Shoou-Yih; McClelland, Mark; Albert, Nancy
Abstract Background The theory of middle managers' role in implementing healthcare innovations hypothesized that middle managers influence implementation effectiveness by fulfilling the following four roles: diffusing information, synthesizing information, mediating between strategy and day-to-day activities, and selling innovation implementation. The theory also suggested several activities in which middle managers might engage to fulfill the four roles. The extent to which the theory aligns with middle managers' experience in practice is unclear. We surveyed middle managers (n  = 63) who attended a nursing innovation summit to (1) assess alignment between the theory and middle managers' experience in practice and (2) elaborate on the theory with examples from middle managers' experience overseeing innovation implementation in practice. Findings Middle managers rated all of the theory's hypothesized four roles as "extremely important" but ranked diffusing and synthesizing information as the most important and selling innovation implementation as the least important. They reported engaging in several activities that were consistent with the theory's hypothesized roles and activities such as diffusing information via meetings and training. They also reported engaging in activities not described in the theory such as appraising employee performance. Conclusions Middle managers' experience aligned well with the theory and expanded definitions of the roles and activities that it hypothesized. Future studies should assess the relationship between hypothesized roles and the effectiveness with which innovations are implemented in practice. If evidence supports the theory, the theory should be leveraged to promote the fulfillment of hypothesized roles among middle managers, doing so may promote innovation implementation.